Moving targets: Negotiations on the EU's energy and climate policy objectives for the post-2020 period and implications for the German energy transition - Oliver Geden; Severin Fischer (Stiftung Wissenschaft und Politik (SWP), 2014)
Since 2007, energy and climate policy has occupied a prominent place on the agenda of the European Union. The so-called '20-20-20 targets' negotiated during the German Council Presidency were the first step towards an integrated policy approach. Because of the long investment cycles in the energy industry and the time needed for the EU to reach agreement on its position in the international climate negotiations, debate on the policy framework for the period beyond 2020 has already begun. In January 2014, the Commission proposed targets of a 40 percent reduction in emissions and a 27 percent share of renewable energy by 2030. However, any decision on a new EU energy and climate strategy ultimately lies with the European Council, in which the 28 heads of state and government have to reach consensus. If one compares the present situation with that before 2007, a shift in priorities becomes evident. Since the onset of the global economic crisis, energy price trends have substantially increased in importance. Negative experiences in global climate negotiations have led to disagreements within the EU over whether unilateral commitments should be made prior to an international agreement. Already it seems likely that the project of long-term transformation to a low-carbon economy will face major difficulties when it comes to practical implementation. By analyzing the decision-making process primarily from the negotiators' perspective this study considers the plausible and probable outcomes of negotiations to establish a new EU energy and climate policy framework. In addition, it explores how the likely scenario of an unambitious EU compromise would affect Germany's 'Energiewende' (energy transition) policy. (SWP Research Paper)
Keywords: 320